THEORY AND PRACTICE OF TRANSLATION IN THE DEVELOPMENT OF PROFESSIONAL COMMUNICATION (KONFERENSIYA, 2026)
This article explores the theory and practice of translation and their role in developing professional communication skills. It highlights how accurate translation bridges cultural and linguistic gaps in global interactions.